SIKAP MASYARAKAT DAN PERSEPSI TENTANG PERILAKU APARATUR TERHADAP MINAT MEMBUAT AKTA TANAH DI KECAMATAN SERANG - Ade Duwi Suryatna; Rd Nia Kania Kurniawati; Agus Sjafari (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
Many people believe that they only have Land and Building Tax (SPPT-PBB) Tax Returns and that their land is legally enforceable. SPPT-PBB is a substitute form for Girik which is no longer recognized after the birth of the Basic Agrarian Law (UUPA). Therefore some of the problems that have been explained do indeed require the activities of making land certificates in order to have land rights with legal force. However, the community considered that to obtain the land certificate was very difficult, took a long time and required very expensive fees. Therefore, the writer wants to follow up on the problem and test it using theory and analyze it quantitatively with the aim of finding the influence of "Community Attitudes and Perceptions About Apparatus Behavior Towards Interest in Making Land Deed in Serang District, Serang City, Banten Province". In this research, attitude theory (Azwar 2013), apparatus behavior theory (Siagian 1994), and interest theory (Ajzen 2005). The samples in this study were 279 respondents who were selected by systematic random sampling based on the 2018 land deed register data in Serang District. The questionnaire was distributed by visiting the respondent's house as the owner of the registered land rights in Serang District. The results of this study are the variable community attitudes (X1) to the interest in making a land deed (Y) obtained a significance value of 0.048 < level 0.05 = Ho rejected, meaning that the variable X1 has a significant influence on the variable Y. Perceptual variable (apparatus) ) to the interest in making a land deed (Y) obtained a significance value of 0.118 > level 0.05 = Ho accepted, meaning that the variable X2 does not have a significant effect on the variable Y. Together variables of community attitudes (X1) and perceptions of apparatus behavior (X2) to the interest in making land deed (Y) obtained a significance value of 0.035 < level 0.05 = Ho rejected, meaning that the variables X1 and X2 have a significant effect on the variable Y